Aggressive Personality Traits and Consumer Brand Sabotage Intentions: A Case Study of Pakistani Consumers - Sadaf Amjad; Nosheen Sarwat (Sustainable Business and Society in Emerging Economies, 2023)
Purpose: This study examines the phenomenon of consumer brand sabotage (CBS), with a particular emphasis on exploring the relationships between aggressive personality traits and intentions to engage in CBS. This study specifically investigates that how hostility, rage, physical aggression, verbal aggression, and customer brand sabotage intentions are interrelated. The study's objective is to provide details on the motivations and actions of those who deliberately take action to harm a brand by eroding consumer associations.